Applicability of maximal ergometer testing and sprint performance in adolescent endurance and sprint trained swimmers - Pinos, A. J.; Fernandes, E. M.; Viana, E.; Logan-Sprenger, H. M.; Bentley, D. J. (Sports, 2021)
Sprint swimming is a short duration, high intensity sport requiring a relatively greater contribution of energy from anaerobic metabolism. Understanding energy system utilization for the classification of a competitive swimmer (sprint or distance) may be useful for both training prescription and event specialization. The relationship between anaerobic swim ergometer testing and adolescent sprint swimming performance has not been investigated. The purpose of this study was to compare the performance and physiological responses during a maximal all-out ergometer test as well as the maximal anaerobic lactate test in a group of sprint vs. middle-distance specialized swimmers. Sixteen (n = 16) competitive swimmers (mean ± standard deviation (SD), age 16.8 ± 0.7 year; body mass 67.3 ± 9.8 kg) were categorized into two gender matched groups: sprint (n = 8) and middle-distance (n = 8). Each athlete performed (1) a 45 s swim ergometer maximal test to determine peak and mean power output (Watts (W)), (2) a MANLT test to determine peak and average velocity as well as the post-exercise lactate response, and (3) a 50 m swim time trial. The sprint group showed a higher mean (p = 0.026) and peak (p = 0.031) velocity during the MANLT. In addition, blood lactate concentration was significantly (p < 0.01) higher in the sprint vs. middle-distance trained group at 3 and 12 min after completion of the MANLT (3-min post 11.29 ± 2.32 vs. 9.55 ± 3.48 mmol/L; 12-min post 8.23 ± 2.28 vs. 7.05 ± 2.47 mmol/L). The power output during the 45 s all-out swimming ergometer test was higher in the sprint trained group. The results of this study demonstrate the anaerobic contribution to sprint swimming measured during an all-out dryland ergometer test.